2011
DOI: 10.1126/scisignal.2002164
|View full text |Cite
|
Sign up to set email alerts
|

A Brand New START: Abscisic Acid Perception and Transduction in the Guard Cell

Abstract: The soluble receptors of abscisic acid (ABA) have been identified in Arabidopsis thaliana. The 14 proteins in this family, bearing the double name of PYRABACTIN RESISTANCE/PYRABACTIN-LIKE (PYR/PYL) or REGULATORY COMPONENTS OF ABA RECEPTOR (RCAR) (collectively referred to as PYR/PYL/RCAR), contain between 150 and 200 amino acids with homology to the steroidogenic acute regulatory-related lipid transfer (START) protein. Structural studies of these receptors have provided rich insights into the early mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
92
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 129 publications
(189 reference statements)
2
92
0
1
Order By: Relevance
“…In response to environmental stress, the plant hormone ABA signals stomatal closure (Zeevaart, 1980;Hirayama and Shinozaki, 2007;Cho et al, 2009;Joshi-Saha et al, 2011). This signaling pathway employs H 2 O 2 as a ROS second messenger (McAinsh et al, 1996;Murata et al, 2001;Zhang et al, 2001;Kwak et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to environmental stress, the plant hormone ABA signals stomatal closure (Zeevaart, 1980;Hirayama and Shinozaki, 2007;Cho et al, 2009;Joshi-Saha et al, 2011). This signaling pathway employs H 2 O 2 as a ROS second messenger (McAinsh et al, 1996;Murata et al, 2001;Zhang et al, 2001;Kwak et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Guard cells use an extensive signal transduction pathway to regulate the aperture of stomata, pores on the surface of leaves that facilitate gas exchange and water loss (Roelfsema and Hedrich, 2005;Joshi-Saha et al, 2011). CO 2 , a necessary reactant for photosynthesis, enters leaves through stomata, whereas water can leave through these same pores via transpiration.…”
mentioning
confidence: 99%
“…Abscisic acid (ABA), a key hormone in plant response to water deficit, is a potent inducer of stomatal closure (3). ABA binds to PYR/PYL/RCAR receptors, which capture protein phosphatases 2C (4), leading to activation of Snf1-related protein kinases 2 such as SnRK2.6/OST1 (5). This protein kinase, in turn, activates several types of membrane proteins involved in stomatal closure such as NADPH oxidases (6,7); the anion channels SLAC1, SLAH1, and SLAH3 (8)(9)(10); and the plasma membrane aquaporin (AQP) AtPIP2;1 (11).…”
mentioning
confidence: 99%
“…drought-sensitive plants revealed that drought-tolerant plants accumulated less ABA when subjected to drought stress, demonstrating differential ABA homeostasis between plant genotypes . As a primary stress hormone, ABA helps to maintain plant water status by activating downstream stress-responsive genes (Hauser et al 2011;Joshi-Saha et al 2011;Fujii and Zhu 2012). Accumulating evidence indicates that ABAmediated drought tolerance is associated with the induction of both regulatory and functional gene products (Shinozaki and Yamaguchi-Shinozaki 2007).…”
Section: Introductionmentioning
confidence: 99%